Satisfaction of Individual Taxpayers in Kathmandu Valley, Nepal - Sunil Man Shakya, (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study investigates the determinants of taxpayer satisfaction among individuals in Kathmandu Valley, Nepal. Based on primary data obtained from 200 respondents through a structured questionnaire, the research utilizes descriptive statistics, reliability analysis, Kaiser-Meyer-Olkin (KMO) measure, Bartlett's test, and multiple regression analysis to assess satisfaction relationships against five key dimensions: Tax Knowledge and Awareness, Perceived Fairness of the Tax System, Ease of Filing and Procedures, Service Delivery and Support, and Transparency and Trust. Results show high reliability among constructs and high explanatory power of the model (R² = 0.804, p < 0.001). Tax Awareness and Tax Knowledge were the only statistically significant predictors of taxpayer satisfaction, while other variables, being positively correlated, were not statistically significant. The results emphasise the critical importance of taxpayer education and awareness in enhancing satisfaction and voluntary compliance with the tax administration in Nepal. Policy implications and recommendations are provided.